1993
DOI: 10.1002/bjs.1800800927
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating external injuries of the oesophagus and pharynx

Abstract: Fifty-one instances of oesophageal perforation were discovered when the records of 10,143 [corrected] patients with external penetrating injuries of the neck, chest and abdomen were reviewed. Of these, 33 resulted from stab wounds, 17 from bullets and one from hyperextension of the neck. There were 15 perforations of the pharynx and 36 of the oesophagus. Oesophagography in a lateral decubitus position demonstrated the perforation in all 16 patients in whom it was used. In 45 patients simple repair within 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…3,6,12,18 The mortality rate in the present series was 7% and both patients died as a result of associated injuries due to firearm wounds rather than from the oesophageal injury per se. This demonstrated that firearm injuries are more devastating than stab injuries.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…3,6,12,18 The mortality rate in the present series was 7% and both patients died as a result of associated injuries due to firearm wounds rather than from the oesophageal injury per se. This demonstrated that firearm injuries are more devastating than stab injuries.…”
Section: Discussionmentioning
confidence: 54%
“…12 It confirms the site of injury, identifies the extravasation from the oesophagus, documents the size of the leak, and demonstrates if it is contained or not. The most commonly used modalities are contrast oesophagography and flexible oesophagoscopy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nach Erfahrung von Hatzetheofilou und Ulrich ist eine primä r konservative Therapie ebenfalls bei kleinen iatrogenen Perforationen durch flexible Instrumente mö glich. Hier kann bei innerer Drainage unter absoluter Nahrungskarenz und antibiotischer Abschirmung eine Heilung zu erzielen sein [9,26]. Als Voraussetzungen fü r eine konservative Therapie gelten nach Junginger und Schulz eine umschriebene, gedeckte Perforation ohne Kommunikation mit einer Kö rperhö hle, die frü hzeitige Diagnosestellung sowie das Fehlen septischer Reaktionen [12,24].…”
Section: Therapieunclassified
“…Diese plastische Dekkung kann vor allem bei grö ßeren Defekten, bei bereits bestehenden entzü ndlichen Verä nderungen der Perforationsrä nder und bei fortgeschrittener Umgebungsreaktion empfehlenswert sein. Die ebenfalls empfohlene plastische Deckung durch Aufsteppen von gestielten Pleura-und Perikardlappen, von Zwerchfellanteilen oder des Magenfundus kann problematisch sein, da aufgrund der fortgeschrittenen Mediastinitis ein Mangel an intaktem Umgebungsgewebe bestehen dü rfte [9,19].…”
Section: Therapieunclassified